An Overview of Approaches to Insurance Data Analysis and Suggestions for Warranty Data Analysis - Luo, Ming; Wu, Shaomin (Recent Patents on Engineering, 2016)
Background: Warranty shares similarities with insurance in many aspects. Research on insurance data analysis has attracted much more attention than on warranty data analysis. Objective: This paper aims to provide a general comparison between warranty and insurance in terms of their coverages, policies and data collection. Method: The paper reviews existing approaches to insurance data analysis with regard to modelling of claim frequency, modelling of claim size and policy pricing. Some recent patents relating to statistical models are also discussed. Results: The paper concludes with suggestions for improving warranty data analysis. Conclusion: Copulas are becoming more widely used in insurance data analysis than in warranty data analysis. The paper suggests some aspects in which copulas can be utilised in improving warranty data analysis.
Keywords: Insurance claim